PENANAMAN KARAKTER AKHLAKUL KHARIMAH (MORAL YANG BAIK) SISWA SEKOLAH DASAR DI SEKOLAH ALAM BANDUNG - Mia Komariah; Syaefudin Sa’ud, Udin; Agustin, Mubiar (Jurnal Penjaminan Mutu, 2024)
This research aims to discover how Sekolah Alam Bandung instills the character of akhlakul kharimah (good morals) in elementary school students. This research used a qualitative approach with a qualitative descriptive method at the Sekolah Alam Bandung, with the research subject being the school principal. The research instrument used was an interview sheet, and the data collection techniques used were interviews and the study of curriculum documents used in schools, data analysis is carried out by means of data collection, data reduction, data presentation and conclusions. The research results show that the Sekolah Alam Bandung has the same goal as schools: to educate the nation's life in an intellectual and moral context. However, what differentiates the Sekolah Alam Bandung from state elementary schools in general in instilling the character of akhlakul kharimah is in the learning process. The character of akhlakul kharimah is instilled using exemplary and habituation methods where the teacher becomes an example in implementing the learning, and evaluation is carried out by observation and reported in the groovy report card portfolio every semester. Apart from that, the main characteristic and the output produced using the motto "The most beautiful school in my life" makes Sekolah Alam Bandung produce happy students studying at school. It is hoped that this research can provide broader insight for readers regarding the moral character of elementary school students at Sekolah Alam Bandung and how the school instills them.